PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Asuransi yang Terdaftar Di Bursa Efek Indonesia Periode 2015 sampai dengan 2017) - Annisa, Mutiara Lusiana; Amalia, Rizki Fitri (Universitas Muhammadiyah Palembang, 2018)
This research purpose to know and explaining the effect of capital structure and profitability stock prices case of studies at the insurance companies that listed on the Indonesia Stock Exchange from period time of 2015 untul 2017. The type of research used is explanatory causality research with quantitative approach. Based on sampling technique “purposive sampling” researcher used 11 companies that meets the criteria. The method of analysis used in this research is statistical descriptive analysis multiple linear analysis. The result of the methods show that the capital structure and profitability have a significant effect on the structure of the stock price. The results of research for capital structure has an insignificant the stock price and profitability has a significant the stock price.